Learning Inequalities during COVID-19: Evidence from Longitudinal Surveys from Sub-Saharan Africa - Hai-Anh H. Dang; Gbemisola Oseni; Alberto Zezza; Kseniya Abanokova (Global Labor Organization (GLO), 2022)
There is hardly any study on learning inequalities during the COVID-19 pandemic in a low-income, multi-country context. Analyzing 34 longitudinal household and phone survey rounds from Burkina Faso, Ethiopia, Malawi, Mali, Nigeria, Tanzania, and Uganda, we find that while countries exhibit heterogeneity, the pandemic generally results in lower school enrolment rates. We find that policies targeting individual household members are most effective for improving learning activities, followed by those targeting households, communities, and regions. Households with higher education levels or living standards or those in urban residences are more likely to engage their children in learning activities and more diverse types of learning activities. Furthermore, we find some evidence for a strong and positive relationship between public transfers and household head employment with learning activities for almost all the countries.
Keywords: D0; H0; I2; O1; 330; COVID-19; education; learning activities; enrolment; sub-Saharan Africa; household surveys